Comparative Analysis of Alternative ODL Delivery Modes using Input-Process-Output Model in ODL Institutions: Evidence From The Open University Of Tanzania - Deus, Ngaruko D. (Advances in Social Sciences Research Journal, 2014)
The production of quality human resources in Africa is crucial in order to cope with continent’s growth potential. ODL institutions are better placed to fill the human resource gap that Africa is likely facing. Many African ODL institutions have accelerated production of sufficient number of qualified graduates at various levels by increasing access to education, especially for those attending postgraduate programmes. Different delivery modes have been used to make learning more flexible and more accessible as much as possible without affecting quality of graduates (output). This paper undertakes a comparative analysis of the three dominant delivery modes for postgraduate programmes at the Open University of Tanzania: distance mode, evening classroom mode and executive classroom mode. The paper applies the Input-Process-Output (IPO) model of learning to assess the extent at which the delivery modes may differentially correlate with motivation to learn and hence desired quantity and quality human resource outputs that Africa lacks. Analysis of variance and regression analyses were done based on data extracted from Students Academic Register Information System from OUT for 94 graduates. The results indicate that there is significant difference in desired educational quality output amongst delivery modes. Higher performers were most associated with executive classroom oriented modes of delivery as compared to evening classroom and distance modes. This study supports the notion that classroom delivery modes facilitate motivation to learn more than distance mode. This paper recommends that for the distance mode of delivery to deliver quality outputs, it must be complemented with online learning facilities.